1998
DOI: 10.1177/00220345980770061101
|View full text |Cite
|
Sign up to set email alerts
|

Pain Maps from Facial Pain Patients Indicate a Broad Pain Geography

Abstract: Two hundred consecutive female patients, who were referred to a university-based facial pain clinic, were asked to mark all painful sites on sketches showing the contours of a human body in the frontal and rear views. The drawings were analyzed with transparent templates containing 1875 (frontal view) and 1929 (rear view) square cells of equal size. The average patient scored 71.8 cells in the frontal and 99.7 cells in the rear view (corresponding to 3.8% and 5.2% of the maximum possible scores). In individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 41 publications
7
77
0
4
Order By: Relevance
“…It is essential to distinguish between patients with recently acquired pain from patients with long-established persistent pain. Individual pain distribution of musculoskeletal craniofacial pain falls into one of three clusters that consist of (a) the region involving the trigeminal dermatomes, (b) the trigeminal and upper cervical dermatomes, and (c) pain sites in addition to those listed above (Turp et al, 1998a). Because patients with TM disorders and widespread pain were least tolerant of pain experimentally induced by cutaneous electrical stimulation over the masseter muscles (Hagberg, 1991), differences in peripheral mechanisms and/or central neural processing between subjects with different pain distributions should be expected.…”
Section: Problems Encountered By Clinical Researchmentioning
confidence: 99%
“…It is essential to distinguish between patients with recently acquired pain from patients with long-established persistent pain. Individual pain distribution of musculoskeletal craniofacial pain falls into one of three clusters that consist of (a) the region involving the trigeminal dermatomes, (b) the trigeminal and upper cervical dermatomes, and (c) pain sites in addition to those listed above (Turp et al, 1998a). Because patients with TM disorders and widespread pain were least tolerant of pain experimentally induced by cutaneous electrical stimulation over the masseter muscles (Hagberg, 1991), differences in peripheral mechanisms and/or central neural processing between subjects with different pain distributions should be expected.…”
Section: Problems Encountered By Clinical Researchmentioning
confidence: 99%
“…Our results confirm previous findings that regions of greater pain reports are located in the upper body areas, both for males and females. However, 69% to 76% of TMD patients also present pain outside of head and facial regions 2,14 . A correlation between OFP and referred pain in other body parts is also described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although the screening protocols of OFP patients include questions about the presence of pain in adjacent facial areas such as head, neck, ears and shoulders, the other body areas are rarely considered by dental professionals. Previous studies have reported an association between OFP and general pain conditions [2][3][4][5][6][7] . An example of those relationships is fibromyalgia, which, if not known, may difficult a successful OFP treatment 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain drawings: After the interview, patients were requested to mark all pain sites on a sketch of the human body. Nine potential pain sites (head, face, neck, shoulders, arms, chest, abdomen, back, and legs) could be distinguished 9,10 . statistical analysis Descriptive statistics were used to characterize the sample, considering the number of medical conditions and painful areas mentioned by individuals.…”
Section: Questionnairesmentioning
confidence: 99%